55. CLINICAL SYMPTOMS OF BORDERLINE PERSONALITY DISORDER AMONG ADOLESCENT INPATIENTS WITH NON-SUICIDAL SELF-INJURY IN NATIONAL INSTITUTE OF MENTAL HEALTH (Vietnam Journal of Community Medicine, 2025)
Objective: To describe borderline personality disorder symptoms in adolescent inpatients with non-suicidal self-injury.Methods: A cross-sectional study was conducted on 52 adolescent inpatients with non-suicidal self-injury at the National Institute of Mental Health, Bach Mai Hospital, from July 2024 to February 2025.Results: The mean number of borderline personality disorder symptoms was 4.7 ± 2.1; 55.8% of patients met ≥ 5 borderline personality disorder criteria. The most common symptoms: recurrent suicidal threats/self-harm behaviors (88.5%), affective instability (82.7%), chronic feelings of emptiness (63.5%), and paranoid ideation/dissociative symptoms (65.4%). Patients with repetitive and more diverse forms of non-suicidal self-injury had a higher percentage of borderline personality disorder symptoms.Conclusion: Most adolescent inpatients with non-suicidal self-injury exhibited multiple borderline personality disorder symptoms, particularly affective instability, recurrent suicidal/self-injurious behaviors, and chronic emptiness. Detailed symptom profiling may help identify high-risk individuals and provide a foundation for early intervention.
Keywords: Non-suicidal self-injury; borderline personality disorder; adolescents.